Accounting for natural disasters from a historical perspective: A literature review and research agenda. (May 2021) - Sargiacomo, Massimo; Servalli, Stefania; Potito, Serena; D'Andreamatteo, Antonio; Gitto, Antonio
This study offers an analysis of published historical research on accounting for natural disasters. Drawing on the insights provided by an examination of 35 accounting/business/economic history and generalist journals, 11 articles have been selected and analysed. The analysis conducted on the scattered literature identified the emerging themes, disasters investigated, periods of time explored and main contributions of published research. The analysis is extended by the examination of some key conferences of interdisciplinary history associations, and of the eventual journals/issues where the papers presented were published. The investigation has also been complemented by a brief selection of books showing historical analyses of diverse disasters, typologies and periods of investigation. The stimuli provided by the study have helped to portray the main features of an open research agenda, highlighting possible future research topics and suggesting ancient and recent disasters' loci to be investigated worldwide.